2021
DOI: 10.1186/s12957-021-02334-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect and mechanism of downregulating the long-chain noncoding RNA TM4SF1-AS1 on the proliferation, apoptosis and invasion of gastric cancer cells

Abstract: Background To investigate long-chain noncoding TM4SF1-AS1 in gastric cancer (GC) tissues and cells. Methods TM4SF1-AS1 in 40 GC tissues and adjacent tissues was detected and compared using real-time fluorescence quantitative PCR (qRT-PCR). TM4SF1-AS1 in MKN28 and SGC7901 GC cells was downregulated using small interfering RNA (shRNA). The cells were grouped into an interference group (shTM4SF1-AS1 group) and a control group (shControl group). MTT an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Recent studies have shown the upregulation of TM4SF1-AS1 and its oncogenicity in several types of cancer, including GC, hepatocellular carcinoma, and lung cancer, but the underlying molecular mechanism is not fully understood [27,28,29]. In the present study, we found that TM4SF1-AS1 is transcriptionally activated in the non-tumorous gastric mucosa of GC patients, suggesting its involvement in the early onset of GC development.…”
Section: Discussionsupporting
confidence: 51%
“…Recent studies have shown the upregulation of TM4SF1-AS1 and its oncogenicity in several types of cancer, including GC, hepatocellular carcinoma, and lung cancer, but the underlying molecular mechanism is not fully understood [27,28,29]. In the present study, we found that TM4SF1-AS1 is transcriptionally activated in the non-tumorous gastric mucosa of GC patients, suggesting its involvement in the early onset of GC development.…”
Section: Discussionsupporting
confidence: 51%
“…High TM4SF1-AS1 expression resulted in the activation of the TM4SF1 and PI3K-AKT pathways in gastric cancer cells, thereby enhancing proliferation, invasion, and EMT 46 . Subsequently, TM4SF1 promoted pancreatic cancer metastasis by regulating DDR1 expression 47 .…”
Section: Discussionmentioning
confidence: 99%
“…T cells are the main cells involved in tumor immunotherapy and are responsible for defense against pathogen infection. It has been reported that TM4SF1-AS1 can exacerbate the progression of lung cancer ( 31 ), hepatocellular carcinoma ( 32 ) and gastric cancer ( 33 ). TM4SF1-AS1, a representative SE-associated lncRNA, was found to be involved in T cell immunity for the first time in the present study.…”
Section: Discussionmentioning
confidence: 99%